2008
DOI: 10.1177/0960327108088975
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric poisonings in southeast of Turkey: epidemiological and clinical aspects

Abstract: Current detailed information about the causes, management, and clinical course of acute childhood poisonings in Turkey is scarce. Therefore, we have conducted a descriptive study of children presenting with acute poisoning to the pediatric emergency department of Dicle University Hospital throughout an 8-month period. Two hundred unselected children with poisoning were evaluated in terms of clinical, epidemiological and socioeconomic aspects. The mean age of patients was 5.7 ± 4.0 years. The majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
31
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 13 publications
11
31
0
10
Order By: Relevance
“…Ozdogan et al 13 found that the highest incidences of poisoning occurred in children in the age group of 13 months to 4 years. In this age group, putting small foreign objects like drugs into mouth by children can cause poisoning.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Ozdogan et al 13 found that the highest incidences of poisoning occurred in children in the age group of 13 months to 4 years. In this age group, putting small foreign objects like drugs into mouth by children can cause poisoning.…”
Section: Discussionmentioning
confidence: 97%
“…In several studies, it has been reported that 51.4%-73.3% of all poisoning cases observed in Turkey involved children <5 years of age. [10][11][12][13] It was observed that in developed countries, the percentage of pediatric emergency service admissions for poisoning was between 0.28% and 0.66%. [8][9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em outras regiões do Brasil e do mundo o chumbinho não aprece como problema de saúde pública tão grave como no Rio de Janeiro, optou-se por separá-lo em nossa análise, mas esta decisão também dificulta a comparação com os resultados de outros estudos. Porém, considerando que o grupo dos "outros pesticidas" representaria aproximadamente o conjunto de agrotóxicos disponíveis em outras regiões, pode-se perceber que a prevalência de cerca de 7% obtida nesta investigação não destoa significativamente dos resultados de outros estudos 6,8,10,15 , ainda que um estudo na Turquia tenha encontrado cerca de 17% de intoxicações por pesticidas entre menores de cinco anos de idade atendidos em um serviço de emergência 16 .…”
Section: Discussionunclassified
“…The identification of the epidemiology and risk factors in childhood poisonings is important for decisions regarding effective preventive measures; however, the epidemiology and characteristics of poisonings in children vary among different nations. [5][6][7][8][9] In addition, little information has been published regarding the differences in poisonings by pharmaceuticals and nonpharmaceuticals in children.…”
mentioning
confidence: 99%